2017
DOI: 10.18632/oncotarget.23054
|View full text |Cite
|
Sign up to set email alerts
|

PTEN loss and level of HER2 amplification is associated with trastuzumab resistance and prognosis in HER2-positive gastric cancer

Abstract: BackgroundTrastuzumab is an active agent against human epidermal growth factor receptor 2 (HER2)-positive gastric cancer (GC). This study aimed to characterize resistance to trastuzumab-based front-line chemotherapy in HER2+ GC patients and to establish factors predictive of this resistance.ResultsAmong 129 HER2+ GC patients, 25% displayed rapid disease progression within 4 months from initiation of therapy. These patients showed a higher rate of signet ring cell histology, bone metastasis, poor performance st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Indeed, in a small case series, a patient with a co-amplification of HER2 and MET was treated with a combination of trastuzumab, crizotinib, and paclitaxel and experienced near-complete disease response [ 99 ], and combined targeted blockade warrants further investigations. Additionally, loss of PTEN expression and low HER2 amplification index have been correlated with primary resistance to first-line trastuzumab-based therapy and poor prognosis in a study involving 129 HER2 positive GC [ 100 ].…”
Section: Biomarkers In Gastro-esophageal Cancer: Where Are We Goingmentioning
confidence: 99%
“…Indeed, in a small case series, a patient with a co-amplification of HER2 and MET was treated with a combination of trastuzumab, crizotinib, and paclitaxel and experienced near-complete disease response [ 99 ], and combined targeted blockade warrants further investigations. Additionally, loss of PTEN expression and low HER2 amplification index have been correlated with primary resistance to first-line trastuzumab-based therapy and poor prognosis in a study involving 129 HER2 positive GC [ 100 ].…”
Section: Biomarkers In Gastro-esophageal Cancer: Where Are We Goingmentioning
confidence: 99%
“…Constitutively activated Akt via PTEN deletion leads to trastuzumab resistance (12)(13)(14). A retrospective study that included 129 patients with HER2-positive gastric cancer treated with first-line trastuzumab-based regimens, indicates that patients with loss of PTEN expression have a significantly shortened median PFS (4.5 vs. 12.4 months) and OS (12.3 vs. 28.9 months) compared with those with intact PTEN expression (15). In our case, pyrotinib has been effective, although the patient demonstrated PTEN deletion and resistance to trastuzumab and lapatinib.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that hsa_circ_0033155 may serve a cancer-suppressive role in NSCLC progression. PTEN, a modulator of cell survival and cell cycle progression, has been identified as a tumor suppressor that is downregulated and mutated in various cancers, including hepatocarcinoma, glioblastoma, ovarian and prostate cancer (13,24,25). Therefore, aberrant hsa_circ_0033155 may be associated with the regulation of PTEN, thus regulating cell biological functions.…”
Section: Discussionmentioning
confidence: 99%